Psychological Stress and Role Management on Construction Technology Industry: Post-Pandemic Challenges - Ariffin, Arihasnida; Mohd Faisal, Nur Nadia; Rubani, Siti Nur Kamariah; Hamzah, Norhasyimah; Zakaria, Normah (semarak ilmu, 2024)
Psychological stress is an unpleasant feeling and emotion for a person who is in a state of restlessness, anxiety, and tension because of the mental or physical stress that occurs. The purpose of this study was to find out the level and factors of psychological stress faced by employees in terms of barriers to the role of company management, particularly in the context of construction technology industry. This study was conducted on construction workers in the district of Hulu Selangor affected by the Covid-19 pandemic. This study uses random sampling referring to the population of selected companies. The study sample was 70 people from a total target population of 70 people. The researcher used the method of distributing questionnaires from google forms medium which contains five-section, namely Part A (demographics of respondents), Part B (psychological stress factors among workers) and Part C (aspects of company management role) is the content for the research instrument. The data collected will be analysed using the Statistical Package for School Science (SPSS) program. Descriptive methods were used to obtain the mean, percentage, frequency, and standard deviation in this study. According to the study's findings, the level of psychological stress among worker’s was a moderate and employees also perceived the psychological stress associated with their managerial responsibilities in the context of construction technology sector. To foster a healthier and more productive workplace, this discovery can offer all parties involved with useful information they can use as a guide to leverage technological solutions and structural adjustments to prevent employees from experiencing psychological stress in the future.